Adjustable autonomy: a systematic literature review - Mostafa S.A.; Ahmad M.S.; Mustapha A. (Springer Netherlands, 2023)
Multi agent systems; Software agents; Adjustable autonomy; Autonomous systems; Autonomy assessments; Dynamic environments; Flexible autonomy; ITS applications; Systematic literature review; Systematic literature review (SLR); Autonomous agents